Functional analysis of two subunits of the putative Mitochondrial RNA Binding complex 1 in Trypanosoma brucei - Kafková, Lucie (Jihočeská univerzita, 2010)
The function of two subunits of the putative mitochondrial RNA binding complex (MRB1) found in parasitic protist Trypanosoma brucei was studied by creating single RNAi knockdowns of both genes as well as assaying the double knockdown cell line, previously obtained in our laboratory.
Functional analysis of two subunits of the putative Mitochondrial RNA Binding complex 1 in Trypanosoma brucei
Keywords: Trypanosoma brucei; RNA editing; mitochondrie; MRB1; protist; Trypanosoma brucei; RNA editing; mitochondrion; MRB1; protist